2017
DOI: 10.1097/rlu.0000000000001546
|View full text |Cite
|
Sign up to set email alerts
|

Estimated Internal and External Radiation Exposure of Caregivers of Patients With Pediatric Neuroblastoma Undergoing 131I Metaiodobenzylguanidine Therapy

Abstract: Caregivers receive both external and internal radiation exposure while providing in-hospital care to children receiving I MIBG therapy for neuroblastoma. However, the internal radiation exposure was negligible compared with the external radiation exposure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Patients who completed the first HDCT/ASCT were evaluated for disease status including an 123 I‐MIBG scan and received HD‐ 131 I‐MIBG treatment 2 weeks prior to the second HDCT as previously described . HD 131 I‐MIBG therapy was planned to be administered for patients who had MIBG‐avid tumors at diagnosis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who completed the first HDCT/ASCT were evaluated for disease status including an 123 I‐MIBG scan and received HD‐ 131 I‐MIBG treatment 2 weeks prior to the second HDCT as previously described . HD 131 I‐MIBG therapy was planned to be administered for patients who had MIBG‐avid tumors at diagnosis.…”
Section: Methodsmentioning
confidence: 99%
“…The first HDCT regimen consisted of melphalan 60 mg/m 2 /d for Patients who completed the first HDCT/ASCT were evaluated for disease status including an 123 I-MIBG scan and received HD-131 I-MIBG treatment 2 weeks prior to the second HDCT as previously described. 13 HD 131 I-MIBG therapy was planned to be administered for patients who had MIBG-avid tumors at diagnosis. 131 I-MIBG was synthesized in Korea Atomic Energy Research Institute (Daejeon, Korea).…”
Section: Tandem Hdct/asct With Hd-131 I-mibg Treatmentmentioning
confidence: 99%
“…Although radiation exposure to the caregiver has been shown to be low and within safe ranges (Gains et al, 2015;Han et al, 2017), several nurses in this study reported reservations when caring for children receiving 131 I-MIBG. The concern was shared by female nurses, more often of child-bearing age.…”
Section: Discussionmentioning
confidence: 76%
“…131 I-MIBG therapy is dosed per/kg, so children who are older receive higher doses of radiation, which in turn, emits higher amounts of radiation to the caregivers. However, nurses and family caregivers overall are exposed to minimal doses of radiation when using appropriate precautions and maintaining minimal time in the room, distance from the patient, and shielding (Gains et al, 2015; Han et al, 2017; Willegaignon et al, 2018).…”
Section: Introductionmentioning
confidence: 99%